IMPLEMENTASI ALGORITMA RIJNDAEL DALAM ENKRIPSI DAN DEKRIPSI GAMBAR DIGITAL BERBASIS WEB - Ade Chandra Saputra; Agus Sehatman Saragih (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
More and more abuse of digital images, data or information that is personal in nature can be easily known by others who are not entitled through digital images. This can cause material and immaterial losses to people whose personal information is misused by others. Then the application applies the Rijndael algorithm to secure digital image images which contain information or data that is personal in nature. In securing digital images, the Rijndael algorithm is used to protect the information contained in these images, this algorithm runs with processes such as SubBytes, ShiftRows, MixColumns, and AddRoundKey. The methodology applied is data collection methods such as field studies and literature studies, then methods of developing Waterfall software (Communication, Planning, Modeling, Construction, and Deployment) for system design. The results of the test analysis get an accuracy value of 100% from the 14 image files tested, all of them were successfully encrypted and decrypted so that it returned to the original form of the original image. For further development, this application can input the data files of other documents and increase the key length to 196 bits and 256 bits